2016
DOI: 10.4328/jcam.3982
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of Disabled Geriatric Health Council Reports

Abstract: ÖzetAmaç: Bu çalışmada, 65 yaş ve üzeri, özürlü sağlık kuruluna başvuran olguların değerlendirilmesi amaçlandı. Gereç ve Yöntem: Çalışmada, özürlü kuruluna başvuran, 3112 olgu retrospektif tarandı, 601 olguya ait dosyalar değer-lendirildi. Bulgular: Başvuruların %53,1'i erkek, %46,9'u kadındır. Ortalama yaş 60 (59± 18,35)'dir. En sık başvuru sebebi, sosyal hizmetler %45,6, özürlü-lük oranının tespiti %21,6'dir. 65 yaş ve üzerinde, hipertansiyon %21,6; diyabet %12,6; kronik obstruktif akciğer hastalığı ve dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
5
0
4
Order By: Relevance
“…Previous studies from Turkey reported that most frequent reason of application to HBRD was to receive a special education report for Individual Education Plans (IEPs) (8,(10)(11)(12)(13). However, the most common reason of application in our study was procuring financial aids (i.e.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Previous studies from Turkey reported that most frequent reason of application to HBRD was to receive a special education report for Individual Education Plans (IEPs) (8,(10)(11)(12)(13). However, the most common reason of application in our study was procuring financial aids (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Severe disability was significantly more common among children younger than 8 years while permanent disability was common among children >3 years. In the Turkish literature, studies related to health board reports for disabled (HBRD) examined the sociodemographic characteristics and frequency of disability of the patients in general, but no study was (8). Another study found that most frequent diagnoses were MR/IDD (36.1%), learning disorders (20.2%) and ASDs (11.1%) among its sample of HBRD applications (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18, The WHO reported that as much as 20% of children and adolescents have a disabling mental disorder worldwide and Intellectual disability is the most common mental disorder evaluated within the scope of disability. 3,[19][20][21] Intellectual Disability begins in childhood and is characterized by impairments in both intelligence and adaptive functioning, with varying severity. Developmental disability is used to describe intellectual and adaptive impairment in infants and preschool children.…”
Section: Introductionmentioning
confidence: 99%